Pengaruh Beban Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan dengan Stres Kerja sebagai Variabel Intervening pada PT Batanghari Barisan Padang - Vivi Nila Sari; Rena Safitri; Eny Sulistyowati (Jurnal Maksipreneur, 2022)
This study aims to determine how much influence workload and work environment partially and simultaneously on employee performance with work stress as an intervening variable. Sampling was conducted by random sampling technique with the Slovin method to determine 74 respondents who are permanent employees of the company. Analysis of this research used multiple linear regression techniques to find the effect of the independent variables on the dependent variable and used path analysis to examine the effect of the intervening variables. The analysis of the research used the Statistical Product and Service Solution (SPSS) version 21. The results of this study indicate that workload has a negative and insignificant effect on work stress, while the work environment has a positive and significant effect on work stress. Furthermore, workload and work environment have a positive and insignificant effect on employee performance partially. Workload and work environment simultaneously have a positive and significant effect on work stress. In line with these results, workload and work environment simultaneously have a positive and significant effect on employee performance. This study also confirms that work stress is not able to mediate the effects of workload and work environment on employee performance respectively.